Solid phase iodine data for sediment cores from METEOR cruises M136 and M137 - Florian Scholz; Hardisty Dalton (PANGAEA, 2023)
Sediment cores were collected on the Peruvian continental margin during Meteor cruises M136 and M137. Solid phase samples were analyzed for iodine concentrations by inductively coupled plasma mass spectrometry after microwave-assisted iodine extraction. Solid phase and pore water iodine data were combined with solid phase and pore water nitrogen and carbon data to characterize iodine biogeochemical cycling in sediments as a function of organic carbon delivery and bottom water oxygen concentrations.